(3Hjf GdJehjd GdESdGej h GdJbdjOjs - (3MSjf eMeO(B, (3SeMGfs; (3CMeO YGQa GdYSGa(B, s ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2015)
(3jVe eGgjI GdeTQhYGJ GdUZjQI, eUGOQ Jehjd GdeTQhYGJ GdUZjQI, GdJehjd GdeUQaj ddeTQhYGJ GdUZjQI, GdJMdjd GdeGdj HgOa EbQGV GdeTQhY GdUZjQ, OQGSGJ GdLOhi GdeGdjI ddeTQhY GdUZjQ, Jehjd GdeTQhYGJ GdUZjQI HCSdhH GdJCLjQ GdJehjdj h GdJCLjQ GdefJgj HGdJedjc, CSGdjH GdJehjd GdESdGej GdCNQi ddeTQhYGJ GdUZjQI , hGbY Jehjd GdeTQhYGJ GdUZjQI aj GdCQOf (B.s
(3GdeQGLY U(B.303s
Keywords: (3GdEbJUGO GdESdGejs; (3GdJehjds; (3GdeTGQjYs; (3GdeTGQjY GdUZjQI(B- (3Jehjds